Reaction of N-alkylisatins with 4-(2,3,4,6-tetra-O-acetyl-β-D-glucopyranosyl)thiosemicarbazide - Nguyen Dinh Thanh; Nguyen Thi Kim Giang (Journal of Chemistry)
Some N-alkylisatins were converted to corresponding thiosemicarbazones by reaction with 4-(2,3,4,6-tetra-O-acetyl-β-D-glucopyranosyl)thiosemicarbazide using microwave-assisted heating method. The structure of products have been confirmed by IR, NMR, and mass spectra.